ANALYSIS OF FACTORS CAUSING EARLY MARRIAGE FOR WOMEN IN PAMEUNGPEUK HAMLET, KADUDAMPIT DISTRICT, SUKABUMI REGENCY - Arifin, Ali Zainal; Maulana, Aris; Wuri, Dewi Kartika; Fajrin, Fahmy; Rahmawati, Indriyani; Nada, Katrin; Fadlyah, Nada; Nurbus, Nurkhayati; Napsiyah, Siti (Universitas Tanjungpura, 2023)
The problem of early marriage is one of the problems that is often found in Indonesia. However, this problem is more common in rural areas than in urban ones. Early marriage is a marriage that occurs between a pair of teenagers, both male and female, who are still not ready physically, physiologically, and psychologically. This study aims to analyze the factors that cause early marriage in Pameungpeuk Hamlet, Kadudampit District, Kabupaten Sukabumi. The method used in this research is a qualitative method with a literature study. To identify the location and informants in this study using a purposive sampling technique. Meanwhile, data collection techniques are in-depth interviews, observations, and case studies. The results of the study show that there are three (3) main factors that cause early marriage, including economic factors, educational factors, and parental factors.